Indigenous Knowledge in Reducing HCN Content in the Processing of Gadung Tubers (Dioscorea hispida) as Student Teaching Materials - Fitri Rahmawati; Ari Ashari; Muhammad Zulhariadi (Jurnal Penelitian Pendidikan IPA, 2023)
The research aims to understand the indigenous knowledge of the community in processing gadung tubers (Discorea hispida) and to identify the most effective variations in reducing HCN content for educational purposes, specifically in the form of an Environmental Knowledge Module for students in the Biology Education program at FKIP Cordova University. The research methodology involves an experimental approach with four core stages: conducting surveys and interviews with the community in Beru Village, Jereweh District, West Sumbawa Regency; developing observation sheets for gadung tuber processing based on local knowledge; and engaging in practical activities with the research team, the community, and two biology education students. The research results, based on the module validation, show an average score of 77.5%, categorizing it as good. The conclusion of the study is that the most effective variation in reducing HCN content involves the addition of 300 grams of salt compared to other variations, along with the inclusion of squeezed castor leaves juice. The practical activities conducted in accordance with the local knowledge of Beru Village community in Jereweh District have progressed well, producing gadung sticks as safe-to-consume food products.